Do Economic Preferences of Children Predict Behavior? - Laura Breitkopf; Shyamal Chowdhury; Shambhavi Priyam; Hannah Schildberg-Hörisch; Matthias Sutter (Institute of Labor Economics (IZA), 2024)
We use novel data on nearly 6,000 children and adolescents aged 6 to 16 that combine incentivized measures of social, time, and risk preferences with rich information on child behavior and family environment to study whether children's economic preferences predict their behavior. Results from standard regression specifications demonstrate the predictive power of children's preferences for their prosociality, educational achievement, risky behaviors, emotional health, and behavioral problems. In a second step, we add information on a family's socio-economic status, family structure, religion, parental preferences and IQ, and parenting style to capture household environment. As a result, the predictive power of preferences for behavior attenuates. We discuss implications of our findings for research on the formation of children's preferences and behavior.
Keywords: C91; D01; 330; social preferences; time preferences; risk preferences; experiments with children; origins of preferences; human capital; behavior